Run sprint interval training improves aerobic performance but not maximal cardiac output - Macpherson, R. E. K.; Hazel, T. J.; Oliver, T. D.; Paterson, D. H.; Lemon, P. W. R. (Medicine & Science in Sports & Exercise, 2011)
Repeated maximal-intensity short-duration exercise (sprint interval training, SIT) can produce muscle adaptations similar to endurance training (ET) despite a much reduced training volume. However, most SIT data use cycling, and little is known about its effects on body composition or maximal cardiac output (Qmax).